2D Schottky Junction between Graphene Oxide and Transition‐Metal Dichalcogenides: Photoresponsive Properties and Electrocatalytic Performance. Issue 6 (13th January 2019) - Zhou, Huawei; Guo, Junxue; Wang, Can; Liu, Xuejing; Shi, Shaozhen; Wei, Jiazhen; Pu, Xipeng; Li, Wenzhi; Zhang, Dafeng; Wang, Jie; Ren, Xiaozhen; Ma, Huiyan; et al.
Abstract: 2D graphene is conductor and not a semiconductor. 2D transition—metal dichalcogenides (TMD) is a semiconductor and not a conductor. Preparing 2D composite material that simultaneously possesses both advantages of graphene and TMD has proven to be challenging. In this work, both 2D‐WS2 /2D‐GO and 2D‐MoS2 /2D‐GO composites with few layer thickness are synthesized. The electronic structure indicates a high content of Mo 4+ 3d5/2 and W 4+ 4f7/2 with lower binding energy in the 2D composite, which is ascribed to partial loss of surface sulfur atoms in 2D composites and the newly formed heteroatomic bond of CWS and CMoS. The Schottky junction between 2D‐GO and 2D‐TMD (2D G‐T junction) is established and exhibits obvious photoelectric responses. Superior electrocatalytic properties of the two 2D‐composites are attributable to the 2D Schottky Junction between 2D‐TMDs and 2D‐GO. Interlayer electronic coupling in 2D Schottky Junction (2D G‐T junction) activates inert sites on the 2D surface of 2D‐TMDs or GO. The power conversion efficiency of dye‐sensitized solar cells (DSCs) based on 2D‐WS2 /2D‐GO is 9.54% under standard solar illumination intensity (AM1.5, 100 mW cm −2 ). The value is one of the highest reported efficiencies for DSCs based on Pt‐free counter electrodes. Finally, 2D‐WS2 /2D‐GO composites exhibit excellent stability as counter electrode of DSCs. Abstract : The Schottky junction between 2D‐TMD (2D‐WS2 and 2D‐MoS2 ) and 2D‐GO is established and exhibits obvious photoelectric responses. Superior electrocatalytic properties of the two 2D‐composites are attributable to the 2D Schottky junction between 2D‐TMDs and 2D‐GO. Interlayer electronic coupling in 2D Schottky junction activates inert sites on the 2D surface of 2D‐TMDs or GO.